Ciprofloxacin Concentrations in Food Could Select for Quinolone Resistance in Klebsiella pneumoniae: An In Vivo Study in Galleria mellonella - Nele Panis; Zina Gestels; Dorien Van Den Bossche; Irith De Baetselier; Said Abdellati; Thibaut Vanbaelen; Tessa de Block; Sheeba Santhini Manoharan-Basil; Chris Kenyon (MDPI AG, 2024)
Background: The use of antimicrobials to treat food animals leaves antimicrobial residues in foodstuffs. The World Health Organization (WHO) defines the acceptable daily intakes (ADIs) of these residues as the dose of these antimicrobials that is safe for an average human to consume on a daily basis. We hypothesized that the lowest dose of ciprofloxacin classified as safe by the WHO could select for ciprofloxacin-resistant strains of Klebsiella pneumoniae in a Galleria mellonella model. Objectives: We aimed to evaluate if the consumption of peri-ADI doses of ciprofloxacin could select for ciprofloxacin-resistant (Ser464Phe, GyrB, ciprofloxacin MIC of 4 µg/mL) compared to -susceptible (isogenic, ciprofloxacin MIC of 0.047 µg/mL) strains of K. pneumoniae in a Galleria mellonella model. Results: A significant increase was seen in the proportion of resistance for the 1× ADI and 1/10th ADI concentrations on day 2 compared to the positive control. Methods: A model of K. pneumoniae infection in G. mellonella larvae was used for the experiment. The larvae were inoculated with K. pneumoniae followed by 10× ADI, 1× ADI, 1/10th ADI, 1/100th ADI, and 1/1000th ADI doses of ciprofloxacin. The isolation of K. pneumoniae colonies was then performed on selective agar plates with and without ciprofloxacin (1 µg/mL). The proportion of colonies with ciprofloxacin resistance was then calculated for each group at 24 and 48 h. Conclusions: We found that, at 48 h, there was an enrichment of K. pneumoniae colonies with ciprofloxacin resistance in the larvae receiving 1× ADI and 1/10th ADI concentrations of ciprofloxacin. These results suggest that the ciprofloxacin MSCselect for K. pneumoniae in this model is 1/10th of the acceptable daily concentration (ADI) dose of ciprofloxacin, which is equivalent to 0.239 ng/µL.